2007
DOI: 10.1128/aem.00974-07
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Bacillus anthracis Spores by Liquid Biocides in the Presence of Food Residue

Abstract: Biocide inactivation of Bacillus anthracis spores in the presence of food residues after a 10-min treatment time was investigated. Spores of nonvirulent Bacillus anthracis strains 7702, ANR-1, and 9131 were mixed with water, flour paste, whole milk, or egg yolk emulsion and dried onto stainless-steel carriers. The carriers were exposed to various concentrations of peroxyacetic acid, sodium hypochlorite (NaOCl), or hydrogen peroxide (H 2 O 2 ) for 10 min at 10, 20, or 30°C, after which time the survivors were q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 17 publications
7
39
1
Order By: Relevance
“…Also, if spores are included in the food stuff, efficiency of wet decontamination is diminished. 58) Treatment using chemical modifier, high pressure and high temperature is enough to decontaminate BCWAs through destruction of toxic and infectious machinery, and it is not necessary to destroy the targets completely to convert to the broken pieces. If the perfect destruction of BCWAs is desired, perfect oxidation can be performed to convert to carbon dioxide, water, nitric acid, sulfuric acid etc.…”
Section: Concept Of Decontaminationmentioning
confidence: 99%
“…Also, if spores are included in the food stuff, efficiency of wet decontamination is diminished. 58) Treatment using chemical modifier, high pressure and high temperature is enough to decontaminate BCWAs through destruction of toxic and infectious machinery, and it is not necessary to destroy the targets completely to convert to the broken pieces. If the perfect destruction of BCWAs is desired, perfect oxidation can be performed to convert to carbon dioxide, water, nitric acid, sulfuric acid etc.…”
Section: Concept Of Decontaminationmentioning
confidence: 99%
“…When employed as a wash water disinfectant, chlorine dioxide has been applied at 5 ppm in water to keep the residue concentration on washed produce within the approved 3-ppm limit [US Food Drug Administration (USFDA) and Center for Food Safety Applied Nutrition, 1998;Pao et al, 2009;21 CFR 173.300]. Peroxyacetic acid (PAA) has been shown to be effective against foodborne pathogens on different produce surfaces (Hilgren et al, 2007;Vandekinderen et al, 2009). Further, it is approved for use in produce wash water at a maximum permissible limit of 80 ppm (21CFR173.315).…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available peracetic acid-based disinfectants contain a considerable amount of hydrogen peroxide that also exhibits antimicrobial activity. PAA is not susceptible to peroxidases and is known to retain its antimicrobial activity in the presence of organic loads or food residues when compared to chlorine (Fatemi and Frank, 1999;Hilgren et al, 2007;Small et al, 2007). Although antimicrobial, the oxidizing ability of these disinfectants, particularly chlorine dioxide and PAA are also associated with discoloration and negative impact on fruit color (Wang et al, 2007;Du et al, 2009;Joshi et al, 2013;Van de Velde et al, 2016;Chen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon applies in particular to oxidative biocides but also the activity of phenols is reduced by organic material like soil, serum, fecal material, and food residues. It has been shown that organic matter decreases the effect of hypochlorites against bacteria, viruses, and fungi [27]. Moreover, body fluids like blood serum can reduce biocide efficacy by neutralizing active agents.…”
Section: Evaluation Of Antimicrobial Efficiency 401mentioning
confidence: 99%